2022
DOI: 10.1242/jcs.258798
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of rRNA in early mouse embryos promotes chromatin reorganization and expression of major satellite repeats

Abstract: During the first cell cycles of the early development, the chromatin of the embryo is highly reprogrammed alongside that embryonic genome starts its own transcription. The spatial organization of the genome is a major process that contributes to regulating gene transcription in time and space, however, it is poorly studied in the context of early embryos. To study the cause and effect link between transcription and spatial organization in embryos, we focused on the ribosomal genes, that are first silent and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
1
1
0
Order By: Relevance
“…These results also provide an interpretation for a previous observation that an unknown nuclear RNA component can sustain the higher-order structure of pericentric heterochromatin 53 , and presents evidence that the ability to maintain chromocenter stability resides at least in part with the transcript itself. Using RNA-FISH, we found that MSR transcripts in ESCs tend to localise close to the periphery of chromocenters, a pattern corroborated by recent studies 54 , 55 . As satellite repeats are under the transcriptional control of pluripotency factors in ESCs 15 , these findings provide a direct connection between cell state and heterochromatin regulation.…”
Section: Discussionsupporting
confidence: 87%
“…These results also provide an interpretation for a previous observation that an unknown nuclear RNA component can sustain the higher-order structure of pericentric heterochromatin 53 , and presents evidence that the ability to maintain chromocenter stability resides at least in part with the transcript itself. Using RNA-FISH, we found that MSR transcripts in ESCs tend to localise close to the periphery of chromocenters, a pattern corroborated by recent studies 54 , 55 . As satellite repeats are under the transcriptional control of pluripotency factors in ESCs 15 , these findings provide a direct connection between cell state and heterochromatin regulation.…”
Section: Discussionsupporting
confidence: 87%
“…These sequences are packed in clusters of condensed chromatin called chromocenters, forming foci heavily stained by the nuclear dye DAPI 14 . During mouse development, the formation of chromocenters at the late 2-cell stage requires a mandatory transcription burst of major satellite sequences, which are then maintained at a low level of transcriptional activity 15 , 16 . Two studies have shown that chromocenters of ESCs are partially marked by H3K27me3, even though H3K27me3 is normally found at facultative heterochromatin 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%